Enhanced Bone Healing Through Systemic Capsaicin Administration: An Experimental Study on Wistar Rats - Bingul, Muhammet Bahattin; Gul, Mehmet; Dundar, Serkan; Tanik, Abdulsamet; Artas, Gokhan; Polat, Mehmet Emrah (Int Scientific Information, Inc, 2024)
Background: The healing of bone defects is a serious challenge worldwide. One branch of dentistry deals with bone defects. Capsaicin has anti-inflammatory, anti-oxidative, and cholesterol-reducing effects. The aim of this study was to evaluate the effects of systemic capsaicin administered at different doses on bone healing. Material/Methods: A total of 32 male wistar rats was used, their weight varying between 250 and 300 g. The rats were randomly divided into 4 groups of 8 rats each. The analyses served to evaluate the effect on healing of different doses of capsaicin and grafts. A significant increase was observed in the number of osteoblasts in the capsaicinapplied groups, compared with the control group. Results: The analyses served to evaluate the effect on healing of different doses of capsaicin and grafts. A significant increase was observed in the number of osteoblasts in the capsaicin-applied groups, compared with that of the control group. The inflammation scores showed a significant difference only in the control group and in the group administered with 50 mg/kg capsaicin (P=0.010). The osteoclast counts were significantly different between all groups. Conclusions: As a result of the analyses, positive effects on bone healing were observed when capsaicin 0.25 mg/kg and 0.50 mg/kg was administered intraperitoneally. However, more studies are needed for more accurate information.
Keywords: Capsaicin; Alveolar Bone Grafting; Bone Matrix